2017
DOI: 10.1038/s41598-017-04150-5
|View full text |Cite
|
Sign up to set email alerts
|

CD31hiEmcnhi Vessels Support New Trabecular Bone Formation at the Frontier Growth Area in the Bone Defect Repair Process

Abstract: CD31hiEmcnhi vessels were a subtype of vessels in the murine skeletal system, with high levels of platelet and endothelial cell adhesion molecule-1 (PECAM-1/CD31) and endomucin (Emcn). They were reported coupling angiogenesis and osteogenesis during bone development. We investigated the distribution of these vessels in rat tibiae and their temporal and spatial distribution during the bone defect repair process to improve our understanding of the importance of these vessels. We confirmed that CD31hiEmcnhi vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…Maybe osteogenic cells from the periosteum and the dura show a differential responsiveness to TGF‐β and other bone‐derived molecules. BCM might as well control other mechanisms relevant for bone regeneration, for example, angiogenesis (Harnik, Miron, Buser, & Gruber, ; Wang et al., ). Overall, collagen membranes have an inherent biological activity by their modulation of the local concentration and activity of TGF‐β and likely other molecules modulating bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maybe osteogenic cells from the periosteum and the dura show a differential responsiveness to TGF‐β and other bone‐derived molecules. BCM might as well control other mechanisms relevant for bone regeneration, for example, angiogenesis (Harnik, Miron, Buser, & Gruber, ; Wang et al., ). Overall, collagen membranes have an inherent biological activity by their modulation of the local concentration and activity of TGF‐β and likely other molecules modulating bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis are data that collagen adsorbes members of the TGF‐β‐superfamily including bone morphogenetic proteins (Freitas et al., ; Hempel et al., ) and that rat calvaria defects are rich in osteoblast progenitors (Wang & Glimcher, ). To which extent cells from the cambium layer of the periosteum (Gruber et al., ), from the blood capillaries (Wang et al., ), and from the dura mater (Petrie Aronin et al., ) contribute to bone formation in the two areas of interest, and if they are differentially targeted by BCM, remains to be determined. Moreover, we cannot rule out that the islands are connected to the host bone via unmineralized, osteoid‐like bridges that are not detected by the segmentation of μCT data.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the choice of animal model, nude mice are ideal for assessing ectopic bone formation, as these immunocompromised animals lack a thymus and do not reject the implant, so that the cells may easily survive after transplantation (34,35). However, rats are used for the classic animal model of bone defect (36,37). In the present study, the X-ray results revealed that the application of BMSCs+CPC and UCMSCs+CPC in the tibia defect model led to improved levels of osteogenesis compared with that in the CPC only group.…”
Section: Discussionmentioning
confidence: 99%
“…Bone defect repair involves a series of complex physiological and pathological processes 2) . Comminuted fractures, bone tumors, extractions and infections often result in local loss of bone tissue in varying degrees 3) .…”
Section: Introductionmentioning
confidence: 99%